Relationship Between Change of Waist and Hip Circumferences Due To Online Lectures in Medical Students of Yarsi University Class of 2019 and The Review in Islamic Perspectives - Nadia Rizki Amalia; Achmad Sofwan; Karimulloh Karimullah (Junior Medical Journal, 2023)
Abstract written in English maximum 250 words. Abstract is made concise and clear with italic format. Abstract contains Online lectures during the COVID-19 pandemic are implemented to reduce face-to-face activities. Online lectures have various impacts on students, one of them is reduced physical activity. The result of online lectures is a change in waist circumference and hip circumference. This may cause obesity in students. The objective of this study is to show the changes that occur and the relationship between changes in the shape of the hip and waist circumference due to online lectures in Medical Students of YARSI University Class of 2019. This study used a descriptive analytic study with a Paired t-Test research design. The sample size used in this study is 72 students. Sampling method used in this study is a purposive sampling method. The research instrument is a sheet recording the waist and hip circumferences measured by a tape and repeated 2 times. Statistical analysis was performed by univariate test and bivariate Paired t-Test. Islamic views regarding changes in the body, one of which is waist and hip circumference due to lifestyle, will be held accountable later. Allah commands His people to be responsible for the body that has been given and take good care of it.